Apple Cider Vinegar in the Combat Against Type 2 Diabetes and Obesity – An Overview of Recent Research - Górska, Magdalena; Kałuża, Izabela; Golemo, Jagna; Serkis, Barbara; Dębińska, Julia; Celichowska, Magdalena; Dziuba, Gabriela; Bogoń, Aleksandra; Ostojska, Magdalena; Miazga, Małgorzata (Quality in Sport, 2024)
ABSTRACT Introduction Apple Cider Vinegar, primarily composed of acetic acid, is gaining more recognition for its possible health advantages, especially its anti-diabetic effects and its beneficial impact on weight loss. Aim of this study The aim of this review is to discuss the current state of knowledge regarding the influence of ACV on glycemic indices and weight management in diabetic and obese patients, explore the possibilities of preventing comorbidities, and assess the safety of ACV consumption. Materials and Methods Research was performed based on Pubmed and Google Scholar databases. The literature was reviewed using the keywords : Apple Cider Vinegar, Diabetes, Glucose, Obesity. Results Studies have confirmed that apple cider vinegar exhibits significant anti-obesity and anti-diabetic properties. It demonstrates dose- and time-dependent effects on reducing fasting glucose, postprandial glucose, glycated hemoglobin, and lipid parameters. It positively impacts weight loss, reducing waist and hip circumference, and enhances tissue sensitivity to insulin. Additionally, apple cider vinegar has been shown to potentiate the effects of metformin, with liquid consumption yielding better results than pill form. Conclusions Although initial findings are encouraging, additional research with a larger participant pool and an extended duration of vinegar consumption is necessary. The brevity of the study period restricts the observation of long-term effects, and a larger sample size would improve the applicability of the findings. Key words: apple cider vinegar; diabetes; glucose; obesity